NeuroThera® Efficacy and Safety Trial – 3 (NEST-3): A Double-Blind, Randomized, Sham-Controlled, Parallel Group, Multicenter, Pivotal Study to Assess the Safety and Efficacy of Transcranial Laser Therapy with the NeuroThera® Laser System for the Treatment of Acute Ischemic Stroke within 24 h of Stroke Onset. Issue 7 (October 2014) - Zivin, J. A.; Sehra, R.; Shoshoo, A.; Albers, G. W.; Bornstein, N. M.; Dahlof, B.; Kasner, S. E.; Howard, G.; Shuaib, A.; Streeter, J.; Richieri, S. P.; Hacke, W.; et al.
Rationale: Transcranial laser therapy is undergoing clinical trials in patients with acute ischemic stroke. The NeuroThera® Efficacy and Safety Trial-1 was strongly positive for 90-day functional benefit with transcranial laser therapy, and post hoc analyses of the subsequent NeuroThera® Efficacy and Safety Trial-2 trial suggested a meaningful beneficial effect in patients with moderate to moderately severe ischemic stroke within 24 h of onset. These served as the basis for the NeuroThera® Efficacy and Safety Trial-3 randomized controlled trial. Aim: The purpose of this pivotal study was to demonstrate safety and efficacy of transcranial laser therapy with the NeuroThera® Laser System in the treatment of subjects diagnosed with acute ischemic stroke. Design: NeuroThera® Efficacy and Safety Trial-3 is a double-blind, randomized, sham-controlled, parallel group, multicenter, pivotal study that will enroll 1000 subjects at up to 50 sites. All subjects will receive standard medical management based on the American Stroke Association and European Stroke Organization Guidelines. In addition to standard medical management, both groups will undergo the transcranial laser therapy procedure between 4·5 and 24 h of stroke onset. The study population will be randomized into two arms: the sham control group will receive a sham transcranial laser therapy procedure and the transcranial laser therapy group will receive an active transcranial laser therapy procedure. The randomization ratio will be 1:1 and will be stratified to ensure a balanced subject distribution between study arms. Study Outcomes: The primary efficacy end point is disability at 90 days (or the last rating), as assessed on the modified Rankin Scale, dichotomized as a success (a score of 0–2) or a failure (a score of 3 to 6).